2017
DOI: 10.1093/hmg/ddx141
|View full text |Cite
|
Sign up to set email alerts
|

Frataxin deficiency impairs mitochondrial biogenesis in cells, mice and humans

Abstract: Friedreich's ataxia (FRDA) is a neurodegenerative disease caused by inherited deficiency of the mitochondrial protein Frataxin (FXN), which has no approved therapy and is an area in which biomarkers are needed for clinical development. Here, we investigated the consequences of FXN deficiency in patient-derived FRDA fibroblast cell models, the FRDA mouse model KIKO, and in whole blood collected from patients with FRDA. We observed decreased mitochondrial copy number in all the three FRDA models tested: cells, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 30 publications
3
56
0
Order By: Relevance
“…Our results demonstrate downregulation of the PGC-1α/NRF1/Tfam pathway in KIKO cerebellum at asymptomatic and symptomatic ages, suggesting that early impaired mitochondrial biogenesis associated with PGC-1α deficiency is an upstream event leading to cerebellar dysfunction in FRDA patients. Interestingly, a recently published paper shows downregulation of mitochondrial biogenesis markers at transcriptional levels, including NRF1 mRNA, Tfam mRNA and mitochondrial DNA, in FRDA patient fibroblasts and blood, as well as in KIKO mouse brain ( Jasoliya et al, 2017 ). This is consistent with our findings in KIKO mouse cerebellum, an affected tissue in FRDA.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrate downregulation of the PGC-1α/NRF1/Tfam pathway in KIKO cerebellum at asymptomatic and symptomatic ages, suggesting that early impaired mitochondrial biogenesis associated with PGC-1α deficiency is an upstream event leading to cerebellar dysfunction in FRDA patients. Interestingly, a recently published paper shows downregulation of mitochondrial biogenesis markers at transcriptional levels, including NRF1 mRNA, Tfam mRNA and mitochondrial DNA, in FRDA patient fibroblasts and blood, as well as in KIKO mouse brain ( Jasoliya et al, 2017 ). This is consistent with our findings in KIKO mouse cerebellum, an affected tissue in FRDA.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we found that the Irp1-or Irp2-null mutation in mouse embryonic fibroblasts (MEFs) caused decreased expression of frataxin (Fxn) and iron-sulfur cluster scaffold protein IscU, two important components of the Fe-S biogenesis machinery (11). Deficiency of Fxn or IscU in human and mouse cells limits mitochondrial function due to the lack of sufficient Fe-S clusters (12,13). Furthermore, IRP depletioninduced deficiency of Fxn and IscU specifically adversely affects the activity of the Fe-S-dependent mitochondrial respiratory chain, while the activities of other Fe-S-dependent enzymes, such as aconitase and xanthine dehydrogenase, are enhanced (11).…”
mentioning
confidence: 99%
“…These PDE inhibitors provide mitochondrial bioenergetics promotion, antioxidant effects, and neuroprotective and neuroregenerative actions. Because decreased mitochondrial biogenesis has been demonstrated in mononuclear cells from peripheral blood of FRDA patients, in FRDA cells and mouse models [64,65], as well as decreased mitochondrial potential membrane and increased ROS production in cerebellar neurons from YG8R mice [46] among other neuronal models [14,27], it would seem that PDE inhibitors may display potential therapeutic benefits in FRDA. Resveratrol, a nonselective PDE inhibitor, increases FXN expression in cellular and mouse models of FRDA and has clinical benefits in FRDA patients by improving oxidative stress and clinical outcomes [50].…”
Section: Discussionmentioning
confidence: 99%